Implantação de biomembrana de colágeno tratada em solução alcalina ou conservada em glicerina a 98% na parede abdominal de equinos - Vulcani, Valcinir Aloisio Scalla; Macoris, Delphim da Graça [UNESP]; Plepis, Ana Maria de Guzzi; Martins, Virgínia da Conceição Amaro; Franzo, Vanessa Sobue; Rabelo, Rogério Elias; de Sant'Ana, Fabiano José Ferreira (FapUNIFESP (SciELO), 2013)
The objective of this research was obtain collagen biomembranes treated in alkaline solution for 72 hours (GE) from tendineous diaphragmatic center of equines and compare its biocompatibility with membranes preserved in a glycerin solution 98% (GG) and membranes do not treated (GC). The membranes were implanted in the internal fascia of recto abdominis muscle of equines and removed, with adjacent tissues, seven, 63 and 126 days postoperative for the preparation of histological slides. The histomorphometric study revealed more intense inflammatory process to GG and CC implants and faster healing for GE implants. It was concluded that the collagen biomembranes treated in alkaline solution is more biocompatible than biomembranes preserved in 98% glycerin.
Implantation of collagen biomembrane treated in alkaline solution or conserved in 98% glycerin in the abdominal wall of horses
Keywords: Biomaterial; Healing; Implant; Reconstructive surgery